Postural Dysfunction During Standing and Walking in Children With Cerebral Palsy: What are the Underlying Problems and What New Therapies Might Improve Balance? - Marjorie Hines Woollacott; Anne Shumway-Cook (Neural Plasticity)
In this review we explore studies related to constraints on balance and walking in children with cerebral palsy (CP) and the efficacy of training reactive balance (recovering from a slip induced by a platform displacement) in children with both spastic hemiplegic and diplegic CP. Children with CP show (a) crouched posture, contributing to decreased ability to recover balance (longer time/increased sway); (b) delayed responses in ankle muscles; (c) inappropriate muscle response sequencing; (d) increased coactivation of agonists/antagonists. Constraints on gait include (a) crouched gait; (b) increased co-activation of agonists/antagonists; (c) decreased muscle activation; (d) spasticity. The efficiency of balance recovery can be improved in children with CP, indicated by both a reduction in the total center of pressure path used during balance recovery and in the time to restabilize balance after training. Changes in muscle response characteristics contributing to improved recovery include reductions in time of contraction onset, improved muscle response organization, and reduced co-contraction of agonists/antagonists. Clinical implications include the suggestion that improvement in the ability to recover balance is possible in school age children with CP.